Phylogeography of Schizopygopsis stoliczkai (Cyprinidae) in Northwest Tibetan Plateau area. Issue 22 (16th October 2017) - Wanghe, Kunyuan; Tang, Yongtao; Tian, Fei; Feng, Chenguang; Zhang, Renyi; Li, Guogang; Liu, Sijia; Zhao, Kai
Abstract: Schizopygopsis stoliczkai (Cyprinidae, subfamily Schizothoracinae) is one of the major freshwater fishes endemic to the northwestern margin of the Tibetan Plateau. In the current study, we used mitochondrial DNA markers cytochrome b (Cyt b ) and 16S rRNA (16S), as well as the nuclear marker, the second intron of the nuclear beta‐actin gene (Act2), to uncover the phylogeography of S. stoliczkai . In total, we obtained 74 haplotypes from 403 mitochondrial concatenated sequences. The mtDNA markers depict the phylogenetic structures of S. stoliczkai, which consist of clade North and clade South. The split time of the two clades is dated back to 4.27 Mya (95% HPD = 1.96–8.20 Mya). The estimated split time is earlier than the beginning of the ice age of Pleistocene (2.60 Mya), suggesting that the northwestern area of the Tibetan Plateau probably contain at least two glacial refugia for S. stoliczkai . SAMOVA supports the formation of four groups: (i) the Karakash River group; (ii) The Lake Pangong group; (iii) the Shiquan River group; (iv) the Southern Basin group. Clade North included Karakash River, Lake Pangong, and Shiquan River groups, while seven populations of clade South share the haplotypes. Genetic diversity, star‐like network, BSP analysis, as well as negative neutrality tests indicate recent expansions events of S. stoliczkai . Conclusively, our results illustrate the phylogeography of S. stoliczkai, implying the Shiquan River is presumably the main refuge for S. stoliczkai . Abstract : This paper is the first intraspecific phylogeography of Schizopygopsis stoliczkai . The phylogenetic analysis reveals two reciprocally monophyletic lineages (i.e. the clade North and South), which are strongly geographically structured.